A quint mode fractal architecture based resonator and its efficacy in the design of multiband bandpass filters. Issue 11 (10th August 2021) - Chakraborty, Riya; Sarkar, Pankaj; Ghatak, Rowdra
Abstract: This paper presents a new approach to design multiband bandpass filters (BPF) using multimode resonator topology inspired from Bamileke fractal architecture in the form of fractal shaped resonator. The proposed resonator architecture exhibits quint mode resonance behavior where resonance frequencies are determined using ABCD matrix. It offers flexibility in terms of choosing passband center frequencies precisely. Initially a second order dual band BPF is presented by suppressing higher order modes using asymmetric feed line. The same structure is used further to implement a triband and a quad band BPF where the input/output coupling circuit is modified to extract the higher order modes. Two stub loaded resonators are also embedded to improve the passband selectivity and to improve upper stopband characteristics. The design guidelines are demonstrated through the external quality factor ( Q e ) and coupling coefficient ( k ) synthesis approach. The developed filters are fabricated and measured to verify the predicted and simulated results. A close agreement is observed between them. The fabricated multiband BPFs has a very compact size, less insertion loss and good return loss profile.